2011
DOI: 10.1111/j.1468-1331.2011.03474.x
|View full text |Cite
|
Sign up to set email alerts
|

Voxel‐wise meta‐analysis of gray matter abnormalities in idiopathic Parkinson’s disease

Abstract: Structural neuroimaging studies on idiopathic Parkinson's disease (IPD) with voxel-based morphometry (VBM) yielded variable and conflicting findings. A systematic review of VBM studies of patients with IPD and healthy control (HC) subjects published in PubMed, ISI Web of Science, Embase, and Medline databases from 1995 to 25 October 2010 was conducted. Coordinates were extracted from clusters of significant gray matter (GM) difference between patients with IPD and HC subjects. Meta-analysis was performed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
78
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 66 publications
5
78
2
Order By: Relevance
“…The neural substrate of motor and cognitive symptoms has been investigated using non-invasive brain imaging such as structural MRI, which can offer the opportunity of identifying early biomarkers. In fact, different MRI techniques are providing mounting evidence of both gray and white matter changes in PD (Cochrane and Ebmeier 2013;Pan et al 2012). …”
Section: Introductionmentioning
confidence: 99%
“…The neural substrate of motor and cognitive symptoms has been investigated using non-invasive brain imaging such as structural MRI, which can offer the opportunity of identifying early biomarkers. In fact, different MRI techniques are providing mounting evidence of both gray and white matter changes in PD (Cochrane and Ebmeier 2013;Pan et al 2012). …”
Section: Introductionmentioning
confidence: 99%
“…11 GM atrophy was increased in one study of patients with PD. 12 Visual assessment of GM changes did not detect differences between the PD subtypes 13 ; however, this methodologic approach may not have been sufficiently sensitive to detect subtle GM changes.…”
mentioning
confidence: 99%
“…Second, the relationship between GM atrophy and clinical symptoms was evaluated in specific regions of interest (ROIs) that were found to be related to PD. 12,[14][15][16] Finally, in regions that showed such a relationship, the association between GM atrophy and functional connectivity within the motor network was examined.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we found that the motor function-related brain areas appear gray matter volume reduction, and PD dyskinesia severity was negatively correlated with its decrease. Pan et al [12] use the meta-analysis study in 17 VBM studies of Parkinson's disease brain cortical atrophy, and a comprehensive analysis found that significant regional gray matter volume reduction is mainly located on the left inferior frontal gyrus (BA47) extended to the left temporal (BA38) and left insula (BA13) in PD patients. Fig.…”
Section: Discussionmentioning
confidence: 99%